Avaliação do impacto da rigidez e da flexibilização normativa, no âmbito do governo federal, sobre a eficiência dos processos de aquisição e contratação - Oliveira, Bruno Ferreira de (2008)
Governmental acquisitions, in Brazil, must be proceeded, as a rule, by means of licitation. Though this principle became constitutional rule only from 1988's Constitution, its existence in Brazilian legal system retraces century XV: by that time, the Filipinas Ordinations ruled it in one only law article. Since then, several rules of law had been incorporated to the Brazilian governmental acquirement system, especially during century XX, hardening the procedures and restricting public manager's discritionarity. Current governmental acquirement system was instituted by the Law nº 8,666/1993, which, however, did not disrupt previous system: with few innovations and more restrictions, it only copied the instruments in the system of the Decree nº 2,300/1986 and previous ones. In its original text, Law nº 8,666/1993 had three licitation procedures for acquisitions - concorrência, tomada de preços, convite - and the exceptional procedures - dispensa and inexigibilidade. Once revealed itself a rigid system, several measures were implemented in order to make it more flexible, having for objectives celerity and price reduction, from discrete alterations of articles of laws to the creation of pregão as a new licitation procedure - initially, there was only the pregão presencial, proceeded face to face - and no longer, the pregão eletrônico, proceeded through web. This research focuses the analysis of the impact of the rigidity / flexibility on Government acquirement system. Despite specialized literature, studies carried through for governmental agencies and state publicity praises the results reached with the use of the pregão eletrônico, the analyses that lead to such conclusion are based on questionable premises. The studies on the efficiency of the pregão eletrônico restrict this concept to its economic dimension, interpreting it as costs reduction. Beyond, the methodology of analysis of this cost reduction has for reference hypothetical values which are also defined by random standards. Here it is, therefore, the objective of this study: to analyze, from the perception of the public managers, the relation between flexibility or rigidity of a procedure and its efficiency, under a multidimensional perspective - taking into consideration, beyond the prices gotten for objects, the time of transaction, the quality of objects and the security of the procedure. From the answers to the questionnaires applied to licitation managers and to members of licitations permanent commissions it was raisen three kinds of information: descriptive data concerning to the ordinal or nominal variables, extracted from the analysis of the objective fields of the questionnaire; not-structuralized, extracted directly from the subjective fields of the questionnaire; e, finally, treated data, extracted from the hypotheses formulated in the research and statistically analyzed. The reflections on the information allowed concluding that the acquirement governmental procedures flexibility extends its efficiency. Restricted the analysis to the pregão eletrônico, it is concluded that it is more efficient under the economic and time perspectives, in relation to the classic procedures; however, under the perspective of the security it does not significantly differs from those; under the qualitative perspective, it is less efficient than the classic procedures, implying in the reduction of the quality of acquired or contracted objects.